Barriers and enablers influencing healthcare professionals' adoption of a biopsychosocial approach to musculoskeletal pain: a systematic review and qualitative evidence synthesis. Issue 8 (August 2021) - Ng, Wendy; Slater, Helen; Starcevich, Cobie; Wright, Anthony; Mitchell, Tim; Beales, Darren
Abstract : Abstract: A substantial evidence–practice gap exists between healthcare professionals learning about the biopsychosocial model of pain and adopting this model in clinical practice. This review aimed to explore the barriers and enablers that influence the application of a biopsychosocial approach to musculoskeletal pain in practice, from the clinicians' perspective. Qualitative evidence synthesis was used. Four electronic databases (CINAHL, EMBASE, MEDLINE, and PsycINFO) were searched. Primary qualitative studies were included if they investigated the experiences of primary healthcare professionals using a biopsychosocial model of musculoskeletal pain care in outpatient settings or their perceptions towards biopsychosocial-oriented clinical practice guidelines. After screening 6571 abstracts, 77 full-text articles were retrieved. Twenty-five studies met the eligibility criteria, reporting the experiences of 413 healthcare professionals (including general practitioners, physiotherapists, and others) spanning 11 countries. Three metathemes were identified that impact the adoption of the biopsychosocial model across the whole of health: (1) at the microlevel, healthcare professionals' personal factors, knowledge and skills, and their misconceptions of clinical practice guidelines, perception of patients' factors, and time; (2) at the mesolevel, clinical practice guideline formulation, community factors, funding models, health service provision, resourcing issues, and workforce training issues; and (3) at the macrolevel, health policy, organizational, and social factors. Synthesized data revealed multilevel (whole-of-health) barriers and enablers to health professionals adopting a biopsychosocial model of pain into practice. Awareness of these multilevel factors may help inform preimplementation preparedness and support more effective implementation of the biopsychosocial model of musculoskeletal pain into clinical practice. Abstract : Supplemental Digital Content is Available in the Text.